Effect of Zn/Y atomic ratio on precipitation behavior and dynamic recrystallization behavior of Mg–Zn–Y alloy under different extrusion temperature - Qiyu Liao; Wenxin Hu; Ruming Chen; Qichi Le (Journal of Materials Research and Technology, 2023)
Precipitation behavior and dynamic recrystallization (DRX) behavior of Mg–Zn–Y alloys with different Zn/Y atomic ratios under different extrsuion temperatures were systematically investigated in this work. The results shows that the types of precipitated phases in the casted alloys are changed with the increase of Zn/Y atomic ratio. After extrsuion, the brittle W-phases in Mg98.7Zn1Y0.3 and Mg98Zn1Y1 alloys are broken into finer particles along the extrusion direction, but the resistance of W-phases to grain growth is weak at higher extrusion temperature. However, Mg97.5Zn1Y1.5 alloy exhibits relatively stable grain size at different extrusion temperatures, due to the significant inhibitory effect of LPSO phases on grain growth at high temperatures. The banded LPSO phases with wide phase spacing can promote DRX behavior via particle stimulated nucleation (PSN) resulting in highest DRX fraction. Nevertheless, the lamellar LPSO phases could effectively hinder the grain boundary migration and dislocation motion, which is against the nucleation and growth of DRX grains. It is precisely due to the influence of LSPO phases on the DRX behavior and its own kinking effect that Mg97.5Zn1Y1.5 alloy has better heat resistance. Mg97.5Zn1Y1.5 alloy exhibits excellent tensile strength and ductility, with ultimate tensile strength (UTS) of 413 MPa, yield strength (YS) of 330 MPa and elongation (EL) of 12.1% after extrusion at 573 K. The good ductility is mainly due to the coordinated deformation ability of the LPSO phase and the activated non-basal slip effect. The synergistic effect of lamellar LPSO phase and kinking deformation effectively refines the microstructure of the alloy and improves the strength.